The work of Almirante and Pixinguinha conducting the radio program O Pessoal da Velha Guarda (1947- 1952): choice of repertoire and arrangements for the popular orchestra (Revista da Tulha, 2017)
This article discusses the performance of Almirante and Pixinguinha conducting the repertoire and the arrangements made by Pixinguinha for the popular orchestra of the radio program O Pessoal da Velha Guarda. The program aimed to disseminate musical styles not conveyed by the media in the 1940s, when other musical styles emerged, some of them influenced by foreign music, such as bolero and samba-canção. Some researchers of the popular music in Brazil at the time, as well as intellectuals and composers, expressed themselves about it, but also looked for ways to promote the repertoire of songs considered by them as “root”, as well as the folkloric music of several regions of Brazil. The singer and radio producer Almirante, together with the musicians who were part of the staff of some of his programs from the 1930s and 1940s, such as Curiosidade Musicais and Orquestras e Musicos do Brasil focused on the design and implementation of the program O Pessoal da Velha Guarda, which was broadcast on Radio Tupi, of Rio de Janeiro, from 1947 to 1952. On the stage of this program, there were musicians and singers part of a regional group of choro and the popular orchestra, led by Pixinguinha.